Edukasi Literasi Pajak dan Akuntansi untuk Meningkatkan Kepatuhan Masyarakat di Kelurahan Betungan Bengkulu - Isma Coryanata; Irwansyah Irwansyah; Abdullah Abdullah; Indah Oktari Wijayanti (Karawo : Journal of Community Service (KJCS), 2026)
This community service activity aimed to improve tax and accounting literacy in order to encourage public compliance in Betungan Village, Kampung Melayu District, Bengkulu City. The main problems faced by the community were the low level of understanding regarding tax obligations and the lack of optimal simple financial recording practices. To address these issues, the program was carried out using educational and participatory approaches through interactive lectures, tax calculation training, discussions, and simulations of simple financial bookkeeping that were easy for the community to understand. The activity involved 100 participants consisting of local residents, MSME actors, village officials, and district officials, and was conducted at the Betungan Village Hall. The results showed a significant increase in participants’ understanding based on comparisons between pre-test and post-test results. Participants also demonstrated improved abilities in calculating taxes and maintaining simple financial records in a more accurate and organized manner. In addition, the activity successfully increased public awareness of the importance of tax compliance and proper financial management. Therefore, this community service program is expected to contribute positively to improving taxpayer compliance and encouraging more orderly, independent, transparent, and sustainable financial management within the community in the future.